Класифікація кримінально-процесуальних санкцій - Сопронюк, О.; Soproniuk, O. (Східноєвропейський національний університет імені Лесі Українки, 2015)
Автор вважає, що наукова класифікація кримінально-процесуальних норм повинна спиратися на загально-теоретичний правовий підхід. За способом реагування на правопорушення кримінально-процесуальні санкції варто змістовно та структурно поділяти на такі види та підвиди: 1) правовідновлювальні: 1.1) скасування або зміна незаконних процесуальних актів; 1.2) примусове виконання обов'язку; 1.3) відшкодування (компенсація) шкоди у кримінальному провадженні (у межах глави 9 КПК України); 2) каральні: 2.1) позбавлення або обмеження прав учасників провадження; 2.2) накладення грошових стягнень; 3) санкції нікчемності. За галузевою приналежністю кримінально-процесуальні санкції диференційовано на: 1) кримінально-процесуальні; 2) кримінально-правові; 3) адміністративні; 4) цивільно-правові; 5) дисциплінарні. Особливість каральних кримінально-процесуальних санкцій полягає у можливості їх поєднання з санкціями того ж виду іншої галузевої приналежності. According to the author of the article scientific classification of criminal procedural norms should be based on general theoretical legal approach. In accordance with the kind of response to the offense violations criminal procedural sanctions should be divided into the following types and subtypes: 1) restoration of rights: 1.1) cancellation or modification of procedural illegal acts; 1.2) enforcement of the obligation; 1.3) refund (compensation) of damages in criminal proceedings (within chapter 9 of Criminal Code of Ukraine); 2) punitive: 2.1) deprivation or restriction of rights of the proceedings; 2.2) impose monetary penalties; 3) the sanction of nullity. According to sectoral affiliation criminal procedural sanctions have been differentiated into: 1) criminal-procedural; 2) criminal-legal; 3) administrative; 4) civil legal; 4) disciplinary. The peculiarity of criminal procedure and penal sanctions is the possibility to combine them with the sanctions of the same kind from another branch of law. By the degree of definiteness criminal procedural sanctions have been divided into: 1) absolutely determined; 2) relatively-defined; 3) alternative. The author concludes that relativelydefined and alternative criminal procedural sanctions dominate in the CPC allowing to individualize the limitation of rights of the guilty person. According to the subject of application the sanctions are divided into: 1) sanctions applied by officials who are subjects of criminal procedure relationships, and 2) the sanctions that are applied to other legal entities. The latter group is used outside criminal proceedings.
Classification of Сriminal Procedural Sanctions
Keywords: норма права; санкція норми права; класифікація; кримінальне процесуальне право; norms of law; the sanction of the rule of law; classification; criminal procedural law